Two conformers of a tyrosine kinase inhibitor (AG-1478) disclosed using simulated UV-Vis absorption spectroscopy. (16th August 2016) - Khattab, Muhammad; Chatterjee, Subhojyoti; Clayton, Andrew H. A.; Wang, Feng
Abstract : A quantum mechanical rationale for the observed UV-Vis spectrum of anti-cancer drug AG-1478 was accomplished using two conformers. Abstract : AG-1478 ( N -(3-chlorophenyl)-6, 7-dimethoxy-4-quinazolinamine) shows promising in vitro and in vivo antiproliferative activity and has gained global interest due to its potent and broad biopharmaceutical activities. An important step towards understanding its spatial and temporal distribution is to determine whether the inhibitors have spectral signatures that might assist in determining the relevant targets and interactions. Its UV-Vis absorption spectra in various solutions have been measured [Khattab et al., Spectrochimica Acta A, 2016, 164, 128]. The present study correlates the UV-Vis spectral signatures with the structure of the drug. Two stable conformers AG-1478B and AG-1478A with close energy values (Δ E = 1.58 kcal mol −1 ) were located on the potential energy surface through rotation of the single C–N bond of the C–NH–C chain of the drug. The present density functional theory (DFT) study reveals that both conformers contribute to the measured UV-Vis absorption spectrum of AG-1478. The conformers, AG-1478B and AG-1478A, were subjected to further study using molecular orbital theory. It is found that although the conformers are close in energy, the anisotropic properties, such as the shape in three dimensional (3D) space, the dipole moment and the orbitals, are apparently different. The excess orbital energy spectrum (EOES) indicates that six core orbitals exhibit significant conformational changes, exhibiting the signatures of the N atoms, i.e., the NH linker N(25) and the quinazoline N(12) . The valence orbitals with significant configurational changes are either due to the local distribution (30a) or delocalization (46a, 76a and 82a (highest occupied molecular orbital (HOMO))).